THE INFLUENCE OF COMMUNICATION, DISCIPLINE, WORK COMPETENCE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Dewi Sulfiana; Eko Nur Fu’ad (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of communication, discipline, work competence, and work motivation on employee performance at CV Maji Furniture Jepara. The research method used is quantitative with an explanatory approach, involving the entire population of 70 employees through a saturated sampling technique. Data collection was carried out using a questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study indicate that communication, discipline, and work competence have a positive and significant effect on employee performance, while work motivation does not have a direct effect on performance. Work motivation is proven to have a significant effect on discipline and work competence, as well as an indirect effect on performance through these two variables, with work competence as the strongest mediator. These findings emphasize the importance of strengthening competence and discipline to improve employee performance. Keywords: Communication; Discipline; Work Competence; Work Motivation; Employee Performance